2014
DOI: 10.3109/07853890.2014.913378
|View full text |Cite
|
Sign up to set email alerts
|

A second duodenal biopsy is necessary in the follow-up of adult coeliac patients

Abstract: After 12-18 months on a gluten-free diet, 8% of the patients do not present a satisfactory histological response; only some of them could have been identified with a serological and/or clinical re-evaluation. Therefore, a duodenal biopsy seems to be the only tool that could identify patients with unsatisfactory histological response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Although the role of a follow-up duodenal biopsy in CD is still unclear,1 we have shown that evaluating recovery of the intestinal lesion is very important 16. Thus, histological grading of villous atrophy could be of help when the initial and the follow-up biopsy cannot be directly compared.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of a follow-up duodenal biopsy in CD is still unclear,1 we have shown that evaluating recovery of the intestinal lesion is very important 16. Thus, histological grading of villous atrophy could be of help when the initial and the follow-up biopsy cannot be directly compared.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Biagi et al showed that the majority of celiac patients do not present a satisfactory histological response and they suggested a duodenal biopsy to be the only tool that could identify patients with unsatisfactory histological response [5]. Additional studies about this approach are mandatory.…”
Section: Histological Follow Upmentioning
confidence: 97%
“…CD occurs only in patients who express HLA-DQ2 and/or DQ8 molecules [4]. The prevalence of CD in adults varies between one in 100 and one in 300 in most parts of the world [5].…”
Section: Introductionmentioning
confidence: 99%
“…those with persisting symptoms despite being on a GFD (1)(2)(3)(4) . Moreover, despite the availability of different non-invasive surrogate markers to assess GFD adherence (24)(25)(26) , there is still no widespread consensus on whether responsibility for coeliac patients' follow-up should be taken by dietitians, primary care physicians, gastroenterologists or tertiary referral centres (1)(2)(3)(4)19,(24)(25)(26)(27)(28) . Moreover, which follow-up modalities to employ are even more controversial.…”
mentioning
confidence: 99%
“…Moreover, which follow-up modalities to employ are even more controversial. Although in clinical practice evaluation of adherence to a GFD can be made by clinical assessment, dietetic review and serology, demonstration of histological recovery on a GFD is also part of the routine follow-up in some centres (19,27,28) .…”
mentioning
confidence: 99%